2008
DOI: 10.1038/ja.2008.83
|View full text |Cite
|
Sign up to set email alerts
|

In Vitro and in Vivo Antitrypanosomal Activitiy of Two Microbial Metabolites, KS-505a and Alazopeptin

Abstract: Our on-going screening program to discover new antitrypanosomal antibiotics has been evaluating compounds isolated from soil microorganisms as well as investigating the antibiotic libraries of the Kitasato Institute for Life Sciences and BioFrontier Laboratories of Kyowa Hakko Kogyo Co., Ltd. We have now discovered two compounds, KS-505a and alazopeptin, which exhibit moderate antitrypanosomal characteristics. We report here the in vitro and in vivo antitrypanosomal activities and cytotoxicities of KS-505a and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
15
0

Year Published

2009
2009
2021
2021

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 29 publications
(15 citation statements)
references
References 17 publications
0
15
0
Order By: Relevance
“…6,7 Animals Female CD1 mice (ICR), 20-25 g, were obtained from Charles River Japan Inc. (Kanagawa, Japan). Animals were placed in groups of four per cage, kept in a room under negative pressure with flow of 0.1-0.2 m sec À1 .…”
Section: Trypanosomesmentioning
confidence: 99%
See 1 more Smart Citation
“…6,7 Animals Female CD1 mice (ICR), 20-25 g, were obtained from Charles River Japan Inc. (Kanagawa, Japan). Animals were placed in groups of four per cage, kept in a room under negative pressure with flow of 0.1-0.2 m sec À1 .…”
Section: Trypanosomesmentioning
confidence: 99%
“…6,7 We have discovered a further three peptide antibiotics, leucinostatin A and B (produced by soil fungi, Paecilomyces sp.) and alamethicin I and tsushimycin (from the antibiotic library) (Figure 1), which show potent or moderate antitrypanosomal properties.…”
Section: Introductionmentioning
confidence: 99%
“…[3][4][5] Pyrenocine A (2) showed the most potent antitrypanosomal activity, with an IC 50 value of 0.12 mg ml À1 (Table 2). Pyrenocine I (1) had a similar antitrypanosomal activity (IC 50 ¼1.8 mg ml À1 ) to the commonly used drug suramin, although it was 10-fold less active than 2.…”
mentioning
confidence: 99%
“…We have previously reported various microbial metabolites exhibiting potent antimalarial [1][2][3][4] and antitrypanosomal properties. [5][6][7] We have recently found that the known 20-membered ring macrodiolide antibiotics, the bispolides, 8 together with new derivatives, exhibit selective antitrypanosomal and potent antimalarial activities, both in vitro and in vivo. Here, we report the antitrypanosomal and antimalarial profiles of bispolides, their derivatives ( Figure 1) and the related 16-membered ring macrodiolide antibiotic as elaiophylin (azalomycin B) 9,10 (Figure 1) in comparison with those of clinically used antitrypanosomal drugs, such as suramin and eflornithine, and two clinically used antimalarial drugs, artemisinin and chloroquine.…”
mentioning
confidence: 99%
“…1, 5 In vivo antitrypanosomal activity for T. b. brucei strain S427 was measured as described previously. 6 Test compounds were solubilized in an aqueous mixture of 10% DMSO-Tween 80 and EtOH (7:3) and administered i.p. to mice on the next day (day 1) following infection with parasites (day 0).…”
mentioning
confidence: 99%